Roll your own. (Economist, 1996)
Reports on scientific measurement being made through virtual instrumentation using a personal computer; LabVIEW, a simple instrument-programming language pioneered by National Instruments; How Anadigics, a specialist semiconductor maker in Warren, New Jersey, went from $220,000 costs for testing chips down to $8,000 with the new technology.